The Tisa initiative: An overview of market access issues - Juan A. Marchetti; Martin Roy (World Trade Organization (WTO), 2013)
This paper aims to provide insights into the market access issues arising in such negotiations. Should TISA negotiations result in participants exchanging the best commitments they have so far undertaken in their preferential trade agreements (PTAs) - a reasonable starting point - 'TISA market access commitments would go well beyond GATS commitments and services offers tabled in the Doha Round. While this would be in itself a significant outcome (especially in terms of predictability and stability), we also highlight, however, that the real economic benefits would be reduced by the fact that a number of participants have already exchanged significant concessions amongst themselves through bilateral PTAs. Further, and more importantly, exchanging 'best PTA' commitments would not meet the participants' most important export interests. These have often remained unaddressed in many of the previous bilateral negotiations or involve countries not currently participating in TISA. Addressing better these export interests would require going beyond an exchange of 'best PTA' commitments among TISA participants - with the more difficult policy and negotiating decisions that this implies - and/or seeking to expand the group of participants. We also discuss the different forms that such a plurilateral agreement may take vis-à-vis the WTO framework.
Keywords: F13; F15; F53; 330; GATS; trade in services; preferential trade agreements